Ethical choice. On Kierkegaard's critique to Kant's moral philosophy - Muñoz Fonnegra, Sergio (Estudios de Filosofía, 2010)
This piece offers a thorough approach to the Existential Ethics of Kierkegaard, and at the same time shows in what moment there comes about a separation from the Moral Philosophy of Kant and operates as a corrective to the latter. From both conceptions of Ethics is presented the problem of moral acting, both in its purely practical dimension (Kant and Kierkegaard) and in its constitutive existential dimension (Kierkegaard), stressing the importance of the election of the self in connection to the principles of morality.